2015
DOI: 10.1021/acs.joc.5b01695
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Metal-Free C–H Activation of Branched Aldehydes and Acylation of Alkenes Using Hypervalent Iodine Compound: A Theoretical Study

Abstract: The mechanism of the C-H activation of aldehydes and the succeeding acylation of an alkene using a hypervalent iodine reagent is investigated by theoretical calculations. In contrast to the initial proposed mechanism, the present calculations show that the hypervalent iodine is the initiator of the radical reaction. The formation of acyl radical is rate-determining, and the resulting radical acts as the chain carrier. The kinetic isotope effect (KIE) of deuterated aldehyde, as well as other experimental observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 76 publications
0
21
0
2
Order By: Relevance
“…It should be noted that substrates such as aldehydes are known to undergo chain reaction processes and this transformation is likely no exception. [15] In summary, the catalytic generation of highly reactive chlorine atoms using photoredox mediated activation of chloride has been achieved. The chlorine atoms engaged with a variety of hydridic C À H bonds including alkanes, alcohols, ethers, ester, amides, aldehydes, and silanes, for the redoxneutral Giese-type addition of alkyl radicals to activated alkenes.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…It should be noted that substrates such as aldehydes are known to undergo chain reaction processes and this transformation is likely no exception. [15] In summary, the catalytic generation of highly reactive chlorine atoms using photoredox mediated activation of chloride has been achieved. The chlorine atoms engaged with a variety of hydridic C À H bonds including alkanes, alcohols, ethers, ester, amides, aldehydes, and silanes, for the redoxneutral Giese-type addition of alkyl radicals to activated alkenes.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…The reaction was completed through the protodeiodination of the iodocyclized intermediates. Keiji Morokuma and co‐workers studied the mechanism of acylation of an alkene catalyzed by hypervalent iodine reagents using theoretical calculations. Hypervalent iodine reagents are first decomposed into free radicals under illumination, which become the transmitter of the reaction steps.…”
Section: Introductionmentioning
confidence: 99%
“…[7] The success of such methods primarily relies on the choice of ap roper HATc atalyst that can chemoselectively abstract hydrogen from aC(O)ÀHbond over amultitude of other CÀ Hb onds present in the molecule. [8] In this context, our laboratory has recently demonstrated that benzoate can serve as aH AT catalyst upon oxidation by ap hotoredox catalyst, thus leading to the selective functionalization of the unactivated C sp 3 À Hb onds. [9] On the basis of this observation, we wondered whether it would be possible for such abenzoyloxy radical to selectively abstract hydrogen from C(O)ÀHbond in the presence of other C sp 3 ÀHb onds in the molecule.W e envisioned that the exploitation of the relative bond dissociation energies (BDE) of these C À Hbonds [BDE for C sp 3 À H = 96.5 kcal mol À1 vs.B DE for C sp 2 (O) À H = 89.4 kcal mol À1 ] [10] would impart kinetic selectivity in such an abstraction event, thereby leading to the selective generation of an acyl radical.…”
mentioning
confidence: 99%